Antenatal screening of depressive and manic symptoms in south Brazilian childbearing women: A transversal study in advance of the pandemic scenario. - Fernanda Schier de Fraga; Beatriz Souza Lima Wan-Dall; Gabriel Henrique de Oliveira Garcia; Henrique Pandolfo; Adelyne Mayara Tavares da Silva Sequinel; Pedro Alvin; Eduardo Jonson Serman; Vivian Ferreira do Amaral (PLoS ONE)
Background The diagnosis of mood disorders (MD) during pregnancy is challenging and may bring negative consequences to the maternal-fetal binomial. The long waitlist for specialized psychiatric evaluation in Brazil contributes to the treatment omission. Almost 20.0% of women treated with antidepressants have a positive screening for bipolar disorder. Therefore, it has been recommended the investigation of depressive and bipolar disorder during prenatal care. Unfortunately, the screening for mood disorders is not a reality in Brazil and many childbearing women remain undiagnosed. The objective of this study is to observe the frequency of MD and the effectiveness of screening scales for routine use by health professionals during prenatal care in high-risk pregnancies. Methodology/principal findings This cross-sectional study included 61 childbearing women in their second trimester who were interviewed using the Edinburgh Postnatal Depression Scale (EPDS) and the Mood Disorder Questionnaire (MDQ). The cut-off point was EPDS ≥ 13 and MDQ ≥ 7 and the SCID-5 was the gold standard diagnosis. MD were diagnosed in 24.6% of the high-risk pregnancies. EDPS was positive in 19.7% and the frequency of major depression was 8.2%. 16.4% of the childbearing women were diagnosed with bipolar disorder, while MDQ was positive in 36.1%. 11.5% of the women had EPDS and MDQ positive. EPDS sensitivity was 80.0% and specificity 92.1%, whereas MDQ presented a sensitivity of 70.0% and specificity of 70.6%. Conclusion/significance There is a high prevalence of MD in high-risk pregnancies. The routine use of EPDS simultaneously to MDQ during antenatal care is effective and plays an important role in early diagnosis, counselling, and promotion of perinatal mental health.